Assistance for Healthy Cultivation of Chili Plants on Sub-Optimal Land in Facing the Impact of Climate Change in Sumbawa Regency: Pendampingan Budidaya Sehat Tanaman Cabai Pada Lahan Sub Optimal Menghadapi Dampak Perubahan Iklim Di Kabupaten Sumbawa - Ieke Wulan Ayu; Ikhlas Suhada; Wening Kusumawardani; Ade Maryam Oklima; Yhosa Novantara; S. Soemarno (Mattawang: Jurnal Pengabdian Masyarakat, 2021)
Environmental stress is a major challenge in sustainable food production, because it can reduce crop productivity, specifically chilies on sub-optimal land. The use of liquid organic fertilizers containing complete macro and micro nutrients is highly needed, so that plants thrive and are healthy and are more resistant to pathogens. This activity aimed to improve the knowledge and skills of farmer group partners about healthy plant cultivation technology on sub-optimal land. Assistance activities were carried out for the Hasrat Indah farmer group in Kerato Village, Unter Iwes District, Sumbawa Regency, during July 2020 by using extension and training methods. The results of the activity indicated that this assistance activity can improve the farmers’ knowledge about healthy cultivation of chilies, and the application of fertilizers at the right time by using liquid organic fertilizers. The successes achieved in the process of empowering farmers in this activity included increasing farmers’ knowledge of soil health, healthy cultivation of chilies, and the application of using liquid organic fertilizers. Abstrak Cekaman lingkungan merupakan tantangan utama dalam produksi pangan berkelanjutan, karena dapat mengurangi produktivitas tanaman, terutama pada tanaman cabe di lahan sub optimal. Penggunaan pupuk organik cair yang mengandung zat hara makro dan mikro lengkap sangat diperlukan agar tanaman tumbuh subur dan sehat serta lebih tahan terhadap patogen. Tujuan kegiatan adalah untuk meningkatkan pengetahuan dan keterampilan mitra kelompok tani terkait teknologi budidaya tanaman sehat di lahan sub optimal. Kegiatan pendampingan dilakukan pada kelompok tani Hasrat Indah di Desa Kerato Kecamatan Unter Iwes Kabupaten Sumbawa, selama bulan Juli 2020 dengan metode penyuluhan, dan pelatihan. Hasil kegiatan menunjukkan bahwa melalui pendampingan dapat meningkatkan pengetahuan petani tentang budidaya sehat pada tanaman cabe, aplikasi pupuk pada waktu yang tepat dengan menggunakan pupuk organik cair. Keberhasilan pemberdayaan petani dalam kegiatan ini adalah petani mengetahui tentang kesehatan tanah, budidaya sehat tanaman cabe, dan aplikasi penggunaan pupuk organik cair.